2013
DOI: 10.1371/journal.pone.0066565
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Combination of alkB Primers to Better Characterize the Distribution of Alkane-Degrading Bacteria

Abstract: The alkane monooxygenase AlkB, which is encoded by the alkB gene, is a key enzyme involved in bacterial alkane degradation. To study the alkB gene within bacterial communities, researchers need to be aware of the variations in alkB nucleotide sequences; a failure to consider the sequence variations results in the low representation of the diversity and richness of alkane-degrading bacteria. To minimize this shortcoming, the use of a combination of three alkB-targeting primers to enhance the detection of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 41 publications
0
27
0
1
Order By: Relevance
“…Alkane-utilizing bacteria are widespread in marine and terrestrial environments. These bacteria generally possess the Alk enzyme system, which is involved in the metabolic pathway for the degradation of alkanes, the main compounds found in petroleum and its derivatives (Jurelevicius et al, 2013). Alkane hydroxylase is a key enzyme in alkane degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Alkane-utilizing bacteria are widespread in marine and terrestrial environments. These bacteria generally possess the Alk enzyme system, which is involved in the metabolic pathway for the degradation of alkanes, the main compounds found in petroleum and its derivatives (Jurelevicius et al, 2013). Alkane hydroxylase is a key enzyme in alkane degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Alkane monooxygenase (AlkB), used as a catabolic marker for alkane degraders in this study, is a membranebound nonhaem diiron monooxygenase and is the first enzyme in the terminal oxidation pathway of alkane (C5-C16) degradation (van Beilen & Funhoff 2007). We used the primer pairs designed by Kloos et al (2006) which have been shown to successfully amplify alkane monooxygenases from a broad range of bacterial phyla in a variety of pristine and polluted ecosystems (Bell et al 2011;P erez-de-Mora et al 2011;Schulz et al 2012;Giebler et al 2013;Jurelevicius et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the alkB gene was detected in 16 strains that showed a band of 100 bp corresponding to this gene (Figure ). As in this work, other studies have used this gene successfully as a biomarker to detect hydrocarbon‐degrading bacteria in different environments …”
Section: Resultsmentioning
confidence: 82%